Universidade acessível: Com a voz os estudantes surdos do ensino médio - De Moura, Adelso Fidelis [UNESP]; Leite, Lúcia Pereira [UNESP]; Martins, Sandra Eli Sartoreto De Oliveira [UNESP] (FapUNIFESP (SciELO), 2017)
Education system has hindered the access to the school and/or bilingual class by deaf people, offering mainly specialized attendance for students of the Child Education and the earlier years of the Elementary School in the second shift. This way of organizing the education, added to the lack of recognizing of deaf students as a minority group collaborates to maintaining them away from the university. This text depicts the access expectations of deaf students to the Higher Education. Participants of this study are seven deaf students enrolled in the High School, at a state public school located on a town of the west of São Paulo State, who use the Brazilian Signal Language (Libras). Data were collected through individual interviews made in Libras, which were filmed for a further transcription into Portuguese language. Gathered material allowed to identify facilitators and obstacles recognized by those students to accessing the higher education. Most part of these students expressed their dream of entering in a university and continuing their studies. Lack of preparation and guidance of the basic school to ensure the need scientific knowledge to this finality, added to the absence of a Libras-Portuguese translator/interpreter in a university context, were considered by the interviewed deaf people as the main obstacles to admission to the university.
Accessible university: The deaf students of secondary education have the floor
Keywords: Accessibility; Brazilian signal language; Deaf people; High school; Higher education; Special education